2020
DOI: 10.1177/1362168820933184
|View full text |Cite
|
Sign up to set email alerts
|

Heritage language learners’ written texts across pair types and interaction mode

Abstract: Task-based research has investigated the learning opportunities (e.g. language related episodes) that emerge during heritage and second language learner interactions during writing tasks. However, to date, it is unknown how these peer interactions involving heritage language learners contribute to written texts. Further, given the rise of social technologies in educational settings, a need exists to examine how interactions in digital platforms affect the production of written texts. To address these … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
6
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 66 publications
2
6
1
1
Order By: Relevance
“…Nonetheless, this modality effect mirrors and further supports the results obtained by Torres (2020), which found that HL learners expressed more difficulty completing communicative tasks in an online environment. Therefore, one possibility for the preference for F2F courses could be due to their comfort with using the HL in oral communication in a F2F context.…”
Section: Discussion Of Research Questionsupporting
confidence: 87%
See 1 more Smart Citation
“…Nonetheless, this modality effect mirrors and further supports the results obtained by Torres (2020), which found that HL learners expressed more difficulty completing communicative tasks in an online environment. Therefore, one possibility for the preference for F2F courses could be due to their comfort with using the HL in oral communication in a F2F context.…”
Section: Discussion Of Research Questionsupporting
confidence: 87%
“…Results show that interactions in the online context led to a higher production of syntactic coordination, which is associated with lower proficiency levels, compared to the more syntactically complex structures produced during the F2F interactions. More importantly, Torres (2020) found that HS students in fact considered communication in the online modality to be more difficult than in the F2F modality. According to the author, this extra layer of complexity may have deeper implications in HL online education, since the students may be allocating their cognitive and linguistic resources not only to the task at hand (in this case, a collaborative writing task) but also to navigating the online format.…”
Section: The Effect Of Context and Modalitymentioning
confidence: 96%
“…Previous research in mixed HL/L2 teaching contexts has focused primarily on student motivation (e.g., O'Rourke and Zhou 2018) and HL/L2 interactions (e.g., Bowles et al 2014;Torres 2020), and only recently on student attitudes, language ideologies, and identities (Leeman and Serafini 2020;Vana 2020). O'Rourke and Zhou's (2018) research suggests that HL learners are less motivated to study their language(s) and less likely to believe in the academic and professional opportunities of studying a language.…”
Section: Previous Research In Mixed Hl/l2 Teaching Contextsmentioning
confidence: 99%
“…The results in both Torres and Cung (2019) and Torres (2020) imply that engaging in task-based collaborative writing in a digital environment (text SCMC mode in this case) can have an impact on how HL-HL and HL-L2 pairs monitor their language production as well as the syntactic complexity of their written texts. Torres (2020) supports theoretical claims in TBLT that the interplay between task environments (FTF, SCMC) and learner factors (HL-HL, HL-L2 pairs) can determine writing outcomes (Manchón 2014). Moreover, Skehan (2016) has argued that the task environment or condition, and not task features that can make a task more or less complex, can play a larger role in how learners respond to task-based instruction.…”
Section: Task-based Collaborative Writing Studies With Hl Learnersmentioning
confidence: 89%
“…Within instructed HL acquisition, a few studies have adopted a TBLT framework to examine how HL learners engage with communicative tasks, which can be in conjunction with corrective feedback, explicit grammar instruction and/or peer interactions (Blake and Zyzik 2003;Kang 2010;Bowles 2011;Bowles et al 2014;Henshaw 2015;Kim et al 2018;Torres 2018Torres , 2020Torres and Cung 2019). These studies have begun to shed light onto how HL learners respond to task features and conditions, including the use of writing tasks as part of the study design (Bowles 2011;Henshaw 2015).…”
Section: Introductionmentioning
confidence: 99%